Combination of the distance and presence modalities in the teaching of foreign students of Stomatology during the outbreak of COVID-19 - Marcia Hortensia Corona Carpio; Zulema Chávez González; Ana Buenaventura Duharte Escalante; Mileidys Arias Portuondo (Centro Provincial de Información de Ciencias Médicas, 2022)
Taking the methodological orientations for the continuity of the school course 2020-2021 inpre-degree as a starting point, during the outbreak of the COVID-19, inthe Stomatology Faculty of Santiago de Cuba strategies were designed aimed at implementing the presence modality for foreign students, specifically in the subjects corresponding to the first semester, where it was possible to combine the education at work and the use of the communication and information technologies, according to academic year and study plan. The proposed system of skills allowed to conclude the unfinished topics and constituted a challenge in contingency situations.